Simulation method, application and system for preparation process of nano layered structure material

By simulating and optimizing the amplitude modulation decomposition process, the preparation of nanolayered structure materials was solved, and the problem of high cost and inability to prepare bulk materials in the prior art was solved, thereby achieving efficient and economical preparation of nanolayered structure materials. .

CN119400310AActive Publication Date: 2025-02-07SHANDONG UNIV SHENZHEN RES INST
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202411440152.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-15
Publication Date
2025-02-07
Estimated Expiration
2044-10-15

AI Technical Summary

Technical Problem

The prior art is difficult to effectively prepare nanolayered structural materials, especially bulk materials, and the cost is relatively high.

Method used

Nanolayered structural materials are prepared by simulating the amplitude modulation decomposition process of macroscopic layered materials. The specific steps include selecting the A-B binary alloy system, setting the component concentration and thickness of the initial layered area, and calculating the component concentration field at different moments until a stable layered structure is formed.

Benefits of technology

The preparation of nanolayered structural materials, especially bulk materials, at a lower cost, is achieved, and the problem that traditional methods cannot prepare bulk materials is solved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119400310A_ABST
    Figure CN119400310A_ABST
Patent Text Reader

Abstract

The invention belongs to the technical field of amplitude modulation decomposition simulation, and particularly relates to a simulation method, application and system for the preparation process of a nano layered structure material. Comprising the following steps: selecting an A-B binary alloy system capable of realizing amplitude modulation decomposition, establishing a discretized layered material, and respectively setting the thickness and component concentration of each layered region; setting amplitude modulation decomposition temperature and boundary conditions, and calculating component concentration fields at different moments; when the material structure is stable, the component concentration field is a layered structure, and the number of layers is more than two times of the number of layers of the initial layered area, it is considered that the nano layered material is successfully prepared. According to the invention, the nanometer layered structure material layered in the thickness direction can be obtained, i.e., the block-shaped material. The problems that the experiment cost of traditional preparation of the nanometer layered structure material is high, and the block nanometer layered structure material cannot be prepared are solved, and a simulation process and parameter optimization method is provided for preparation of the block nanometer layered structure material.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of amplitude modulation decomposition simulation, and in particular relates to a simulation method, application and system for the preparation process of nano-layered structure materials. Background Art

[0002] The information disclosed in this background technology section is only intended to enhance understanding of the overall background of the invention and should not necessarily be regarded as an admission or any form of suggestion that the information constitutes the prior art already known to those skilled in the art.

[0003] The microstructure of a material is a crucial factor in determining its properties. In recent years, nano-layered materials have attracted considerable attention due to their exceptional mechanical and physical properties. Current discoveries include: the formation of microscopic layered nanotwin structures can significantly enhance material strength while retaining plasticity; nano-layered alloys can enhance strength without significantly reducing electrical conductivity, a feat unattainable with traditional strengthening methods; and nano-layered copper-based alloys exhibit unprecedented advantages in high electrical conductivity, yield strength, uniform elongation, thermal stability, shear damage resistance, casting defect tolerance, wear resistance, impact toughness, and even ultra-high-speed tensile properties.

[0004] Currently, the main methods for preparing micro-layered materials include stack rolling, chemical vapor deposition, exfoliation, and hydrothermal methods. Each of these methods has some shortcomings and is difficult to prepare bulk materials. Spinodal decomposition refers to a metal processing method that decomposes a solid solution into a structure with micro-regions of different compositions after appropriate heat treatment. It has the potential to prepare micro-layered structures, but how to use spinodal decomposition to obtain micro-layered materials still requires a large amount of experimentation and is relatively costly. Summary of the Invention

[0005] In response to the deficiencies of the prior art, the present invention provides a method, application, and system for simulating the preparation process of nano-layered structure materials. The method simulates the spinodal decomposition process of macro-layered materials and optimizes the parameters for preparing nano-layered structure materials by spinodal decomposition.

[0006] In order to achieve the above object, the technical solution of the present invention is:

[0007] In a first aspect, a method for simulating the preparation process of a nano-layered structure material comprises the following steps.

[0008] S1. Select an AB binary alloy system that can achieve spinodal decomposition, establish a discretized layered material, and set the thickness and component concentration of each initial layered region. The component concentration of each initial layered region is within the non-equilibrium concentration range of the spinodal decomposition concentration.

[0009] S2. Setting the spinodal decomposition temperature and boundary conditions, and calculating the component concentration field at different times based on the component concentration, thickness, the free energy of component A in the AB binary alloy phase, the free energy of component B in the AB binary alloy phase, and the interaction energy between component A and component B in the AB binary alloy phase;

[0010] S3. When the component concentration field of the material structure is stable, it is a layered structure, and the number of layers of the layered structure is more than twice the number of layers of the initial layered region in S1, and there are at least two layered structure component concentrations at different equilibrium concentrations, it is considered that the nanolayered material is successfully prepared.

[0011] Optionally, in S1, the alloy system includes one of an iron-chromium alloy, a titanium-niobium alloy, a manganese-copper alloy and an aluminum-based alloy.

[0012] Optionally, the structural layers of the layered material include, from top to bottom in the thickness direction, a first layer, a first transition layer, a second layer, a second transition layer and a third layer.

[0013] Optionally, the concentration of component A is the highest in the first layer, the concentration of component A is the lowest in the third layer, and the concentration of component A in the second layer is between the first layer and the third layer.

[0014] Optionally, in the structural layer, the concentration of component A in the first layer, the second layer and the third layer remains unchanged in the thickness direction, the concentration of component A in the first transition layer in the thickness direction changes uniformly between the first layer and the second layer, and the concentration of component A in the second transition layer changes uniformly between the second layer and the third layer.

[0015] Optionally, the basis for judging whether the component concentration is within the adjustable decomposition concentration range is: chemical free energy density function f ch The second derivative of the component concentration c is less than 0, that is,

[0016] Optionally, the initial thicknesses of the first layer, the second layer, and the third layer of material vary depending on the material properties. A more common range is that the thickness ratio of the first layer, the first transition layer, the second layer, the second transition layer, and the third layer of material is 1:(1-1.5):(2-3):(1-1.5):1, where the thickness of the first layer is tens to one hundred nanometers.

[0017] Optionally, in S2, the amplitude modulation decomposition temperature is a set constant value;

[0018] Optionally, in S2, the boundary condition is a three-dimensional periodic boundary condition.

[0019] Optionally, in S2, the free energy of component A in the AB binary alloy phase, the free energy of component B in the AB binary alloy phase, and the interaction energy of components A / B in the binary alloy phase are obtained by querying and calculating a thermodynamic database.

[0020] Optionally, in S2, the component concentration field at different times is calculated using the Cahn-Hilliard equation.

[0021]

[0022] x is the position along the x direction after the layered material is uniformly discretized in space;

[0023] t is the time of amplitude modulation decomposition;

[0024] c A (x, t) is the mole fraction of the A component in the structural layer of the layered material as a function of x and t;

[0025] M = 1 is the mobility;

[0026] F is the total free energy;

[0027] ξ is the Langevin noise term of structural fluctuations, and the Langevin noise term ξ has a mean of 0 and a variance of 10 -6 Gaussian distribution.

[0028] The expression of total free energy F is:

[0029]

[0030] where f ch is the chemical free energy density;

[0031] κ = 0.1 is the gradient energy coefficient;

[0032] dV is the volume of the infinitesimal element, dV = dx*dy*dz, dx, dy, dz represent the lengths of the infinitesimal element in the x, y, and z directions, respectively. In our current numerical integration, dx, dy, dz can be considered as the discretized grid sizes in the x, y, and z directions, that is: dx = Δx, dy = Δy, dz = Δz, so dV is equal to the volume of the infinitesimal element after discretization of the grid, that is: dV = Δx*Δy*Δz.

[0033] The expression for chemical free energy density is:

[0034]

[0035] Where R is the ideal gas constant;

[0036] T is the thermodynamic temperature;

[0037] β is the AB binary alloy phase;

[0038] is the free energy of component X in the β phase, where X is component A or component B;

[0039] is the binary interaction energy between component A and component B in the β phase;

[0040] and From the Thermodynamics Database

[0041] Optionally, in S3, the thickness of a single layered structure is 3 to 60 nm.

[0042] Optionally, the method further includes the following step: S4: if the component concentration field obtained in S3 does not meet the requirements, resetting the component concentration and thickness of each layered region in S1 and / or the spinodal decomposition temperature in S2 to perform simulation.

[0043] The second aspect is the application of the simulation method of the above-mentioned nano-layered structure material preparation process in the preparation of nano-layered materials.

[0044] After evaluating in S3 whether the layered structure meets the dimensional requirements of the nano-layered structure, the material having the component concentration and thickness set in S1 is heat-treated at the spinodal decomposition temperature set in S2 until a layered structure having a stable component concentration in S3 is formed.

[0045] In a third aspect, a simulation system for the preparation process of nano-layered structure materials includes:

[0046] The setting module is used to select the A component and the B component, establish the discretized layered material, and set the component concentration and thickness of each layered region;

[0047] The calculation module is used to set the spinodal decomposition temperature and calculate the component concentration field at different times based on the component concentration and thickness of the layered material, the free energy of component A in the AB binary alloy phase, the free energy of component B in the AB binary alloy phase, and the interaction energy of components A / B in the AB binary alloy phase.

[0048] The judgment module is used to judge whether the component concentration field is a layered structure according to the component concentration field when the material structure is stable, and to evaluate whether the layered structure meets the scale requirements of the nano-layered structure.

[0049] The beneficial effects of the present invention are:

[0050] The present invention is applicable to any material capable of spinodal decomposition. Based on the principles presented, a suitable initial structure is designed, and after spinodal decomposition, a layered nanostructured material, i.e., a bulk material, is obtained. This overcomes the high experimental costs and inability to prepare bulk nanostructured materials in traditional methods of preparing nanostructured materials, providing a simulation process and parameter optimization method for preparing bulk nanostructured materials. BRIEF DESCRIPTION OF THE DRAWINGS

[0051] The accompanying drawings, which constitute a part of the present invention, are used to provide a further understanding of the present invention. The exemplary embodiments of the present invention and their descriptions are used to explain the present invention and do not constitute improper limitations on the present invention.

[0052] Figure 1 This is the initial structure diagram of the material in Example 1.

[0053] Figure 2 This is a diagram of the layered structure of the gradient region in Example 1.

[0054] Figure 3 This is the final structure diagram of the material in Example 1 after spinodal decomposition.

[0055] Figure 4 This is a flow chart of the simulation method for the preparation process of the nano-layered structure material in Example 1.

[0056] Among them, 1, the first layer; 2, the second layer; 3, the third layer; 4, the first transition layer; 5, the second transition layer. DETAILED DESCRIPTION

[0057] It should be noted that the following detailed descriptions are exemplary and intended to provide further explanation of the present invention. Unless otherwise specified, all technical and scientific terms used herein have the same meaning as commonly understood by those skilled in the art to which the present invention belongs.

[0058] It should be noted that the terms used herein are only for describing specific embodiments and are not intended to limit the exemplary embodiments according to the present invention. As used herein, unless the context clearly indicates otherwise, the singular form is intended to include the plural form. In addition, it should be understood that when the terms "comprise" and / or "include" are used in this specification, they indicate the presence of features, steps, operations, devices, components and / or combinations thereof.

[0059] Example 1

[0060] like Figure 4 As shown, a simulation method for the preparation process of nano-layered structure materials includes the following steps.

[0061] S101. Select a titanium-niobium alloy from an alloy system capable of achieving spinodal decomposition, wherein component A is Nb and component B is Ti. Establish a discrete layered material, including a first layer, a first transition layer, a second layer, a second transition layer, and a third layer. Set the component concentration and thickness of each layered region. The concentration of the Nb component in the first layer is the highest, the concentration of the Nb component in the third layer is the lowest, and the concentration of the Nb component in the second layer is between the first and third layers.

[0062] Moreover, in the structural layer, the component concentrations in the first, second, and third layers remain constant in the thickness direction. The Nb component concentration in the first transition layer changes uniformly from the first layer to the second layer in the thickness direction. The Nb component concentration in the second transition layer changes uniformly from the second layer to the third layer in the thickness direction. The concentrations of each layer are within the adjustable decomposition concentration range, that is, the initial concentration satisfies the chemical free energy density function f ch The second-order derivative of the concentration c is less than 0, that is,

[0063] The initial thicknesses of the first layer, the first transition layer, the second layer, the second transition layer and the third layer vary depending on the properties of the materials. A more common range is that the thickness ratio of the first layer, the first transition layer, the second layer, the second transition layer and the third layer is 1:(1-1.5):(2-3):(1-1.5):1, where the thickness of the first layer is tens to one hundred nanometers.

[0064] S102, setting the spinodal decomposition temperature and three-dimensional periodic boundary conditions, and calculating the component concentration field at different times based on the component concentration, thickness, the free energy of the Nb component in the Nb-Ti binary alloy phase, the free energy of the Ti component in the Nb-Ti binary alloy phase, and the interaction energy of the A / B components in the Nb-Ti binary alloy phase;

[0065] Specifically, a phase field model for calculating component concentration fields is established based on the Cahn-Hilliard equation.

[0066] The Cahn-Hilliard equation is:

[0067]

[0068] Among them, c Nb is the mole fraction of Nb element;

[0069] M = 1 is the mobility;

[0070] F is the total free energy;

[0071] ξ is the Langevin noise term of structural fluctuations, and the Langevin noise term ξ has a mean of 0 and a variance of 10 -6 Gaussian distribution.

[0072] The expression of total free energy F is:

[0073]

[0074] Among them, f ch is the chemical free energy density;

[0075] κ = 0.1 is the gradient energy coefficient;

[0076] dV is the volume of the infinitesimal element, dV = dx*dy*dz, dx, dy, dz represent the lengths of the infinitesimal element in the x, y, and z directions, respectively. In our current numerical integration, dx, dy, dz can be considered as the discretized grid sizes in the x, y, and z directions, that is: dx = Δx, dy = Δy, dz = Δz, so dV is equal to the volume of the infinitesimal element after discretization of the grid, that is: dV = Δx*Δy*Δz.

[0077] Chemical free energy density f ch The expression is

[0078]

[0079] Where R = 8.314 J / (mol·K) is the ideal gas constant;

[0080] T is the thermodynamic temperature, i.e. the set spinodal decomposition temperature;

[0081] is the free energy of component X (Nb or Ti) in the β phase (Nb-Ti binary alloy phase);

[0082] represents the binary interaction energy of components Nb and Ti in the β phase, which are all from the thermodynamic database. The specific expressions are as follows:

[0083]

[0084] Since M is a constant in formula (11), formula (11) can be transformed into:

[0085]

[0086] It can be approximated by the first-order forward difference:

[0087]

[0088] Where Δt is the grid size after uniform discretization of time;

[0089] N is the number of time steps.

[0090] And because For the second-order partial derivative It can be approximated by the second-order central difference:

[0091]

[0092] Among them, Δx is the grid size along the x direction after the space is uniformly discretized,

[0093] x iThe meaning is: divide the interval [0,a] evenly into m x The length of each segment Then x i =i×Δx,i=0,1,…,m x , where a and m x It is up to the researchers to decide;

[0094] y j The meaning is: divide the interval [0,b] evenly into m y The length of each segment Then y j =j×Δy,j=0,1,…,m y , where b and m y It is up to the researchers to decide;

[0095] z k The meaning is: divide the interval [0,c] evenly into m z The length of each segment Then z k =k×Δz, k=0,1,…,m z , where c and m z It is up to the researchers to decide;

[0096] t n The meaning is: divide the interval [0,d] evenly into m t The length of each segment Then t n =n×Δt,n=0,1,…,m t , where d and m t It is up to the researchers to decide.

[0097] S103. From the simulation results, we can get the corresponding component concentration field c at different times t. Nb (x, t), based on the component concentration field when the material structure is stable after a sufficient number of iterations, it is judged whether the component concentration field is a layered structure, and whether the layered structure meets the scale requirements of the nano-layered structure is evaluated: if there are at least two layered structure component concentrations at different equilibrium concentrations, and the number of layers of the layered structure is more than twice the number of layers of the initial layered region in S101, and after deducting the thickness of the transition layer, the thickness of a single layered structure is 3 to 60 nm (according to the definition of nano-layered materials, the thickness of each layer can be different), the nano-layered material is considered to be successfully prepared; if it does not meet the scale requirements of the nano-layered structure, the initial conditions are changed for simulation to examine the component concentration field under different time steps.

[0098] S104. Obtaining conditions that meet the dimensional requirements of the nano-layered structure, that is, the conditions required for preparing the nano-layered structure of the Nb-Ti alloy.

[0099] Example 2

[0100] The simulation was performed according to the method in Example 1. The simulation program consists of two parts: a core program (involving the solution of the Cahn-Hilliard governing equations) and a parameter file. The core program is located in the cluster and can be edited remotely through the "Visual Studio Code" software. The parameters are submitted to the cluster using the "PowerByte" software. The core program in the cluster reads the parameters and performs the numerical simulation.

[0101] like Figure 1 As shown, the initial layered material includes two elements, Nb and Ti, and includes, from top to bottom, a first layer 1 with a Nb concentration of 65 at.% and a thickness of 30 nm, a second layer 2 with a Nb concentration of 50 at.% and a thickness of 90 nm, and a third layer 3 with a Nb concentration of 35 at.% and a thickness of 30 nm; a first transition layer 4 with a thickness of 30 nm is placed between the first layer 1 and the second layer 2, so that the Nb concentration transitions from 65 at.% to 50 at.%, and a second transition layer 5 with a thickness of 30 nm is placed between the second layer 2 and the third layer 3, so that the Nb concentration transitions from 50 at.% to 35 at.%, so the total thickness of the initial layered material is 210 nm, and the initial concentrations of each layer are all within the adjustable decomposition concentration range, that is, the initial concentrations satisfy the chemical free energy density function f ch The second derivative with respect to concentration c is less than 0:

[0102] The spinodal decomposition temperature is set to 650 K, the boundary conditions are periodic boundary conditions (specifically, the leftmost boundary is connected to the rightmost boundary, the topmost boundary is connected to the bottommost boundary, and the frontmost boundary is connected to the backmost boundary, so the simulated material is a bulk material with a three-dimensional structure), and the spatiotemporal evolution of the concentration state is obtained by numerically solving the Cahn-Hilliard equation.

[0103] The order of spinodal decomposition is: composition gradient change area → component fraction close area → component fraction difference area. The speed of spinodal decomposition is obtained by solving the control equation to obtain the microstructure at different times, and then calculating the difference in microstructure at adjacent times. In a homogeneous system, the closer the initial concentration is to the equilibrium concentration, the slower the system evolution speed. For example, in the second layer 2 (the Ti concentration in this area is close to the Nb concentration, as shown in Figure 2), the spinodal decomposition speed is the same as the initial concentration of the equilibrium concentration. Figure 1 The middle region in the figure has Ti and Nb both at 50 at.%). The region with a large difference in component fractions refers to the region with a large difference in Ti and Nb concentrations, such as Figure 1 The first layer is 1 and the third layer is 3.

[0104] During the spatiotemporal evolution, influenced by the compositional gradient, the driving force for spinomodulation (the first-order variation of the system's free energy with respect to its composition) is large in this region and remains positive or negative until it reaches equilibrium concentration (where the chemical free energy reaches its minimum). Therefore, the spinomodulation morphology in this region is layered.

[0105] because Figure 1 The initial structure is unstable in the current given environment, so it will spontaneously evolve towards the equilibrium state. In this embodiment, the equilibrium is not reached at 9s (a certain moment in the process of evolving towards the equilibrium state), as shown in FIG. Figure 2 As shown, the thickness of the non-layered parts at the upper and lower positions of the bulk material is about 30 nm, and the thickness of the non-layered part in the middle position is about 60 nm.

[0106] Since the chemical free energy has two minimum values ​​in spinodal decomposition, that is, there are two equilibrium concentrations, two layered structures with different component concentrations can be formed in the thickness direction ( Figure 2 and Figure 3 (represented by red and blue in the figure). Figure 2 In the structure shown, the first transition layer and the second transition layer first evolve into a layered structure, and then remain stable during the entire spinodal decomposition evolution process; while the upper and lower adjacent regions are still in the early stages of spinodal decomposition. These layered structures will serve as boundary conditions for the evolution of the adjacent regions, inducing the adjacent regions to evolve towards another equilibrium concentration, gradually forming a layered structure in the adjacent regions, and finally forming at 12 minutes. Figure 3 In the bulk nano-layered structure material shown, the concentration of the components of each layer structure is stable and is at or close to the equilibrium concentration. Since the induction directions of the two adjacent layer structures are different during the spinodal decomposition process, the two adjacent layers are at two equilibrium concentrations of spinodal decomposition.

[0107] After deducting the thickness of the transition layer from the uniform layered structure of each component, the remaining thickness is 15nm, 3nm, 15nm, 9nm, 3nm, 36nm, 36nm, 3nm, 18nm, 3nm, 18nm from bottom to top. The number of layers is more than twice that of the initial layered area, so it can be considered that a nano-layered material has been produced; among them, the phase boundary thickness of the spinodal decomposition material is about 3nm, so after deducting the thickness of the transition layer of 3nm, the thickness of more than 3nm is still obtained, indicating that a stable nano-layer has been formed.

[0108] This can guide the actual preparation process of nano-layered materials. The initial layered material can be obtained through laser printing: powders with different component concentrations are prepared, and the initial structure is obtained by laser printing. The composition is then analyzed using the energy dispersive spectrometer of a scanning electron microscope to verify that the composition distribution of the initial layered material is consistent with the initial state of the simulation. The initial layered material is then aged at the simulated temperature (650K). The composition of the material after different aging times (fine-tuned based on the 12 minutes obtained in the simulation process) is analyzed to determine the time required to obtain the layered structure and the initial structure.

[0109] Example 3

[0110] A simulation system for a nano-layered structure material preparation process, used to implement the simulation method for a nano-layered structure material preparation process in Example 1, comprising:

[0111] The setting module is used to select the A component and the B component, establish the discretized layered material, and set the component concentration and thickness of each layered region;

[0112] The calculation module is used to set the spinodal decomposition temperature and calculate the component concentration field at different times based on the component concentration and thickness of the layered material, the free energy of component A in the AB binary alloy phase, the free energy of component B in the AB binary alloy phase, and the interaction energy of components A / B in the AB binary alloy phase.

[0113] The judgment module is used to judge whether the component concentration field is a layered structure according to the component concentration field when the material structure is stable, and to evaluate whether the layered structure meets the scale requirements of the nano-layered structure.

[0114] The foregoing description is merely a preferred embodiment of the present invention and is not intended to limit the present invention. Those skilled in the art will readily appreciate that various modifications and variations of the present invention are possible. Any modifications, equivalent substitutions, or improvements made within the spirit and principles of the present invention are intended to be within the scope of protection of the present invention.

Claims

1. A method for simulating the preparation process of nano-layered structure materials, characterized in that: The steps include: S1. Select an AB binary alloy system that can achieve spinodal decomposition, establish a discretized layered material, set the thickness and component concentration of each layered region respectively, and the component concentration of each initial layered region is within the non-equilibrium concentration of the spinodal decomposition concentration; S2, setting the amplitude modulation decomposition temperature and boundary conditions, and calculating the component concentration field at different times according to the component concentration, thickness, free energy of component A in the AB binary alloy phase, free energy of component B in the AB binary alloy phase, and interaction energy between component A and component B in the AB binary alloy phase; S3. When the component concentration field of the material structure is stable, it is a layered structure, and the number of layers of the layered structure is more than twice the number of layers of the initial layered region in S1, and there are at least two layered structure component concentrations at different equilibrium concentrations, it is considered that the nano-layered material is successfully prepared.

2. The method for simulating the preparation process of nano-layered structure materials according to claim 1, characterized in that: The alloy system includes one of an iron-chromium alloy, a titanium-niobium alloy, a manganese-copper alloy and an aluminum-based alloy.

3. The method for simulating the preparation process of nano-layered structure materials according to claim 1, characterized in that: The structural layers of the layered material include the first layer, the first transition layer, the second layer, the second transition layer and the third layer from top to bottom in the thickness direction; the concentration of component A in the first layer is the highest, the concentration of component A in the third layer is the lowest, and the concentration of component A in the second layer is between the first layer and the third layer.

4. The method for simulating the preparation process of nano-layered structure materials according to claim 3, characterized in that: In the structural layer, the concentration of the components in the first layer, the second layer and the third layer is constant in the thickness direction, the concentration of the components in the first transition layer in the thickness direction changes uniformly between the first layer and the second layer, and the concentration of the components in the second transition layer changes uniformly between the second layer and the third layer; Optionally, the thickness ratio of the first layer, the first transition layer, the second layer, the second transition layer and the third layer is 1:(1-1.5):(2-3):(1-1.5):1, wherein the thickness of the first layer is tens to one hundred nanometers.

5. The method for simulating the preparation process of nano-layered structure materials according to claim 4, characterized in that: In S2, the amplitude modulation decomposition temperature is a set constant value; Optionally, the boundary condition is a three-dimensional periodic boundary condition.

6. The method for simulating the preparation process of nano-layered structure materials according to claim 1, characterized in that: The free energy of component A in the AB binary alloy phase, the free energy of component B in the AB binary alloy phase and the interaction energy between component A and component B in the AB binary alloy phase are obtained by querying and calculating the thermodynamic database.

7. The method for simulating the preparation process of nano-layered structure materials according to claim 1, characterized in that: In S2, the component concentration field at different times is calculated by the Cahn-Hilliard equation; Optionally, in S3, the thickness of a single layered structure is 3 to 60 nm.

8. The method for simulating the preparation process of nano-layered structure materials according to claim 1, characterized in that: The method further includes step S4: if the component concentration field obtained in S3 does not meet the requirements, the component concentration and thickness of each layered region in S1 and / or the amplitude modulation decomposition temperature in S2 are reset to perform simulation.

9. Use of the method for simulating the preparation process of nano-layered structural materials according to any one of claims 1 to 8 in preparing nano-layered materials.

10. A simulation system for the preparation process of nano-layered structure materials, characterized in that: A setting module is used to select the A component and the B component, establish a discretized layered material, and set the component concentration and thickness of each layered area; A calculation module is used to set the amplitude modulation decomposition temperature and calculate the component concentration field at different times according to the component concentration and thickness of the layered material, the free energy of the A component in the AB binary alloy phase, the free energy of the B component in the AB binary alloy phase, and the interaction energy of the A / B components in the AB binary alloy phase; The judgment module is used to judge whether the component concentration field is a layered structure according to the component concentration field when the material structure is stable, and to evaluate whether the layered structure meets the scale requirements of the nano-layered structure.

Citation Information

Patent Citations

  • Simulation calculation method for reaction characteristics of nano energetic material

    CN116646016A

  • Method of producing nanoparticles, method of producing thermoelectric material, and thermoelectric material

    US20160126440A1